Anterior retropharyngeal plate screw fixation with bilateral anterior transarticular screws for odontoid fractures ... a new comprehensive technique. (3rd July 2017) - Patkar, Sushil
Abstract: Introduction: A certain group of odontoid fractures (Anderson and D' Alonzo Type-2) are usually offered surgical treatment. Common surgical option is an anterior odontoid screw. Some of the fractures are not suitable for anterior odontoid screw (anterior oblique, displaced distal fragments and those with atlantoaxial instability) and these are usually offered posterior transarticular screws (Magerl's) or posterior atlantoaxial screw rod/plate fixation (Goel-Harms technique). Posterior surgery involves atlantoaxial fixation with an indirect attempt to reduce and fuse the fracture . Posterior surgery has a risk of injury to the vertebral arteries, hemorrhage from the paravertebral venous plexus and the C2 root ganglion. Methods: A direct anterior submandibular retropharyangeal approach with open reduction and fixation (ORIF) using a customized variable screw placement (VSP) plate was used to realign and fix the fracture fragments in compression mode under direct vision. Twenty patients of type-II odontoid fractures (unsuitable for anterior odontoid screw) underwent an anterior retropharyngeal approach with anterior variable screw position (VSP) plate and screw fixation and eight amongst them, who had associated atlantoaxial instability underwent additional bilateral anterior transarticular screws. Results: All patients treated by this technique had 100% fracture site bone union without any implant failure. Longest follow-up has been for 3 years. Conclusion: Anterior retropharyangeal approach allows direct fracture fragment realignment under vision with an opportunity to fix in compression mode using the VSP plate, which ensures early fusion across the type-II odontoid fracture. Any associated instability can be treated by additional bilateral anterior transarticular screws. The approach is simple and safe without any risk to the vertebral arteries and biomechanically appealing.